Locally Controlled Release of Methotrexate and Alendronate by Thermo-Sensitive Hydrogels for Synergistic Inhibition of Osteosarcoma Progression - Shan, Hongli; Li, Ke; Zhao, Duoyi; Chi, Changliang; Tan, Qinyuan; Wang, Xiaoqing; Yu, Jinhai; Piao, Meihua (Frontiers in Pharmacology, 2020)
Osteosarcoma is a serious primary bone malignant tumor that can easily affect children and adolescents. Chemotherapy is one of the important and feasible clinical treatment strategies for the treatment of osteosarcoma at present, which is severely limited due to insufficient retention time, poor penetration ability, and serious side effects of current anti-tumor drug preparations. In this work, a novel injectable thermo-sensitive hydrogel (mPEG45–PLV19) loaded with methotrexate and alendronate, and the sustained release at the tumor site synergistically inhibited the progression of osteosarcoma. The mPEG45–PLV19 shows excellent physical and chemical properties. Compared with other treatment groups, the in vivo treatment of Gel+ Methotrexate + Alendronate effectively inhibited the growth of tumor. More importantly, it significantly reduced bone destruction and lung metastasis caused by osteosarcoma. Therefore, this injectable thermo-sensitive hydrogel drug delivery system has broad prospects for osteosarcoma chemotherapy.